If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 1) + 3x = 6x + 3 Reorder the terms: 3(1 + 2x) + 3x = 6x + 3 (1 * 3 + 2x * 3) + 3x = 6x + 3 (3 + 6x) + 3x = 6x + 3 Combine like terms: 6x + 3x = 9x 3 + 9x = 6x + 3 Reorder the terms: 3 + 9x = 3 + 6x Add '-3' to each side of the equation. 3 + -3 + 9x = 3 + -3 + 6x Combine like terms: 3 + -3 = 0 0 + 9x = 3 + -3 + 6x 9x = 3 + -3 + 6x Combine like terms: 3 + -3 = 0 9x = 0 + 6x 9x = 6x Solving 9x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 9x + -6x = 6x + -6x Combine like terms: 9x + -6x = 3x 3x = 6x + -6x Combine like terms: 6x + -6x = 0 3x = 0 Divide each side by '3'. x = 0 Simplifying x = 0
| 12=1/3(4x-3) | | 8(m+2)= | | 112000=-40x^2+4400x | | 6-13x+6x^2=0 | | 5(4x-1)-9x=50 | | p(x)=-40x^2+4400x | | f(x)=x(3x+4)+3 | | 429/x=21/100 | | 4(2n-5)/3=20 | | 1.5q=-6.8 | | 20+6n=150-4n | | 5p+11+7p=107 | | 5g-16=g(4g-4) | | -p(3p+5)= | | -1+2x=-4x+23x | | 6x(6x+3)=48 | | 8x=67 | | 32+20x= | | 10=5v-3v | | x^7y^9/y^2 | | 8x-4x+5=3 | | 420=12X*X | | -4(2f+11)=44 | | y^-9/y^-3 | | -8k(2-d)= | | 4-a=4 | | -108+11x=-x+132 | | 3r(-t-2)= | | 6h-25=35 | | 3.50+2.50+3t=26.50 | | 10x-3=4x+8 | | 3-3*2=0 |